IMPAK MEDIA SOSIAL TERHADAP TINGKAH LAKU SOSIAL PELAJAR DI KOLEJ VOKASIONAL - Ab Halim, Fazlinda; Muslaini, Mohammad Siraj Munir (Online Journal for TVET Practitioners, 2018)
Social media networks have created a phenomenon on the internet that helps maintain relationships with other users. However, in recent times there are a handful of teenagers who are too obsessed with the use of social media that result in the phenomenon of social media addiction. Therefore, this study is conducted to examine the impact of social media on student's social behaviour in vocational colleges. The study was quantitative. The sample of the study consisted of 345 vocational college students. The research instrument involved a set of questionnaires that contained 41 items and used the Likert scale as a measure. The mean score analysis and standard deviation are used to see the purpose of using and the impact of social media among students. T-test is used to see the impact of social media impact on gender-based social behaviour. There are social media effects on students such as wasting time, depression and stress as students are exposed to immoral videos and pictures. Furthermore, there was no significant difference in the impact of social media on students based on student gender based on t-test. In conclusion, social media has had a negative impact on the students. Thus, high awareness needs to be applied to students to curb social behaviour problems.